Number of emerged seedlings and seedling longevity of the non-recruiting, Critically Endangered Håyun lågu Tree Serianthes nelsonii Merr. (Fabales: Leguminosae) are influenced by month of emergence - Thomas E. Marler; April N. Cascasan (Journal of Threatened Taxa, 2015)
Emergence and longevity of seedlings beneath Guam’s only known Håyun lågu Tree Serianthes nelsonii were studied to determine the fate of every observed seedling during 2013.  Newly emerged seedlings were marked with wire stakes every 15 days, then the stakes were collected at each seedling upon death.  Longevity of each seedling was calculated from the marked ending and emergence dates.  The least number of newly emerged seedlings was recorded at the end of the dry season, and the greatest number of newly emerged seedlings was recorded in the beginning of the rainy season.  More than half of the year’s 374 seedlings died in less than 30 days.  Seedling longevity ranged from a mean of 31 days for seedlings that emerged in May to 78 days for seedlings that emerged in June.  Our results reveal that the baseline level of recruitment potential of the lone survivor of this species on Guam is substantial, and underscore the need for further research to determine the factors associated with the acutely limited seedling lifespan.